Can Good Corporate Governance Influence the Firm Performance? Empirical Study from Indonesia Transportation Firms - Muhammad Fakhri Musyaffa Budiman; Astrie Krisnawati (AFRE (Accounting and Financial Review), 2021)
Good corporate governance is one factor for the company to improve its performance and maximize shareholder value. The principles of transparency, accountability, responsibility, independence, and fairness are guidelines that must be used by all corporate entities in every company activities; therefore, they can run effectively and efficiently. However, the data shows that the implementation of good corporate governance in Indonesia is still low. Policies and regulations made by the government and companies can improve the low level of good corporate governance. Hence it can improve company performance, especially in terms of financial performance. This study aims to determine the effect of good corporate governance through managerial ownership, independent commissioners, and the board of directors on the company's financial performance through Return on Assets in transportation sub-sector companies listed on the Indonesia Stock Exchange. The data collection method uses secondary data in the form of company annual reports from 2017-2019. The The data analysis technique used regression analysis with panel data. The research findings show that managerial ownership, independent commissioners, and the board have no effect on financial performance as proxied by Return on Assets.Good corporate governance merupakan salah satu faktor bagi perusahaan untuk meningkatkan kinerja perusahaan dan memaksimalkan nilai pemegang saham. Prinsip transparansi, akuntabilitas, responsibilitas, independensi, dan fairness merupakan pedoman yang harus digunakan oleh seluruh entitas perusahaan dalam setiap aktivitas perusahaan, agar dapat berjalan secara efektif dan efisien. Namun data menunjukkan bahwa penerapan good corporate governance di Indonesia masih rendah. Tingkat good corporate governance yang rendah dapat diperbaiki melalui kebijakan dan regulasi yang dibuat oleh pemerintah dan perusahaan sehingga dapat meningkatkan kinerja perusahaan terutama dalam hal kinerja keuangan. Penelitian ini bertujuan untuk  mengetahui pengaruh good corporate governance melalui kepemilikan manajerial, komisaris independen, dan dewan direksi terhadap kinerja keuangan perusahaan melalui Return on Asset pada perusahaan sub sektor transportasi yang terdaftar di Bursa Efek Indonesia. Metode pengumpulan data menggunakan data sekunder berupa laporan tahunan perusahaan dari tahun 2017-2019.  Teknik analisis data menggunakan analisis regersi dengan data panel. Temuan penelitian menunjukkan kepemilikan manajerial, komisaris independen, dan dewan direksi tidak berpengaruh terhadap kinerja keuangan yang diproksikan dengan Return on Assets DOI: https://doi.org/10.26905/afr.v4i1.6017